Context-dependent genomic locus effects on antibody production in recombinant Chinese hamster ovary cells generated through random integration - 우현지 (The Graduate School, Ajou University, 2024)
High-yield production of therapeutic proteins using Chinese hamster ovary (CHO) cells requires stable cell line development (CLD). CLD typically uses random integration of transgenes; however, this results in clonal variation and subsequent laborious clone screening. Therefore, site-specific integration of a protein expression cassette into a desired chromosomal locus showing high transcriptional activity and stability, referred to as a hot spot, is emerging. Although positional effects are important for therapeutic protein expression, the sequence-specific mechanisms by which hotspots work are not well understood. In this study, we performed whole- genome sequencing (WGS) to locate randomly inserted vectors in the genome of recombinant CHO cells expressing high levels of antibodies and experimentally validated these locations and vector compositions. The integration site was characterized by active histone marks and potential enhancer activities, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) mediated indel mutations in the region upstream of the integration site led to a significant reduction in specific antibody productivity by up to 30%. Notably, the integration site and its core region did not function equivalently outside the native genomic context, showing a minimal effect on the increase in exogenous protein expression in the host cell line. We also observed a superior production capacity of the recombinant cell line compared to that of the host cell line. Collectively, this study demonstrates that developing recombinant CHO cell lines to produce therapeutic proteins at high levels requires a balance of factors including transgene configuration, genomic locus landscape, and host cell properties.
학위논문(석사)--분자과학기술학과,2024. 2
Keywords: Cell line development; Chinese hamster ovary (CHO); Hot spot; Random integration